Psychological features and social adaptation of patients with the tremor form of Parkinson’s disease - V. A. Bogacheva; D. V. Zakharov; I. V. Buriak (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2022)
The aim of the study was to study the personality characteristics and psychological state of patients with tremulous hyperkinesis in Parkinson’s disease. We studied men and women aged 49 to 75 years with an established diagnosis of «Parkinson’s disease» of a tremulous (main group) and akinetic-rigid form (control group), stages 1-2 according to Hyun and Yar. To study the psychological state of patients, the Giessen personality questionnaire was used, which made it possible to take into account personal, intrapsychic and socio-psychological variables, as well as to investigate their corresponding characteristics; to establish relationships between intra- and interpersonal variables; to correlate personality traits with interpersonal interaction, social behavior, social attitudes and reactions of the individual. To study the level of social adaptation of patients, a questionnaire of social maladaptation associated with tremor was selected, which made it possible to assess the social consequences of existing disorders, as well as the real severity of tremor. Psychological factors play a significant role in the formation and course of Parkinson’s disease (PD). The study of social adaptation in patients with tremor in PD was first conducted. The study of the personality characteristics of patients with PD showed that, regardless of the form of the disease, all patients with PD are characterized by a decrease in the perception of their social reputation, attractiveness, popularity, respect for others, and the ability to achieve their goals; lack of long-term attachments, lack of sociability, poor ability to surrender, poor fantasy. Only patients with an akinetic-rigid form are characterized by humility, obedience, complaisance, patience, distrust, distancing from other people. Patients with combined tremor are more prone to anxiety than patients with isolated tremor. Shivering hyperkinesis causes social disadaptation and self-stigmatization of patients.